Multilocular cystic renal neoplasm of low malignant potential extending into the perinephric adipose tissue - Khaled Abdelfattah Murshed; Mohammed Akhtar; Mohamed Ben-Gashir (Elsevier, 2019)
Multilocular cystic renal neoplasm of low malignant potential (MCRNLMP) is a rare variant and a distinct subtype of clear cell renal cell tumors that has a favorable outcome. Most of the cases present with a low pathologic stage at diagnosis (T1 or T2). It is unusual for this tumor to extend into the perinephric adipose tissue, renal sinus fat or renal vein. There are very few cases reported in the literature to have a higher pathologic stage (pT3 and above) at diagnosis. Here, we report a case of MCRNLMP with unusual rare finding in which the tumor has extended into the surrounding perinephric adipose tissue. Keywords: Multilocular cystic renal neoplasm of low malignant potential, Multilocular cystic renal cell carcinoma, Perinephric fat invasion